Metal limitation and toxicity at the interface between host and pathogen. Issue 6 (29th September 2014) - Becker, Kyle W.; Skaar, Eric P.
Abstract Metals are required cofactors for numerous fundamental processes that are essential to both pathogen and host. They are coordinated in enzymes responsible for DNA replication and transcription, relief from oxidative stress, and cellular respiration. However, excess transition metals can be toxic due to their ability to cause spontaneous, redox cycling and disrupt normal metabolic processes. Vertebrates have evolved intricate mechanisms to limit the availability of some crucial metals while concurrently flooding sites of infection with antimicrobial concentrations of other metals. To compete for limited metal within the host while simultaneously preventing metal toxicity, pathogens have developed a series of metal regulatory, acquisition, and efflux systems. This review will cover the mechanisms by which pathogenic bacteria recognize and respond to host‐induced metal scarcity and toxicity.